Effect of DMDF on the PM emission from a turbo-charged diesel engine with DDOC and DPOC. (15th June 2015) - Geng, Peng; Yao, Chunde; Wang, Quangang; Wei, Lijiang; Liu, Junheng; Pan, Wang; Han, Guopeng
Highlights: A new technical route on the reductions of smoke emissions and PM was introduced. Smoke emissions and PM from turbo-charged diesel engine with DMDF were measured. Interior relation on dry-soot, smoke opacity and PM was analyzed. Effects of DMDF, DDOC and DPOC on smoke emissions and PM were investigated. Particle number and mass concentrations and size contribution with DMDF were realized. Abstract: This study is aimed to investigate the combined application of diesel methanol dual fuel (DMDF) and a simple after-treatment for reducing particulate matter (PM) emissions of a diesel engine. The effects of DMDF, a double diesel oxidation catalyst (DDOC) and a DOC closely coupled with a particulate oxidation catalyst (POC) in series (DPOC) on smoke emissions, particulate mass and number concentrations and size distributions were analyzed. Tests were conducted on a 4-cylinder turbo-charged, inter-cooling, mechanical in-line fuel injection pump diesel engine modified to DMDF combustion mode. Testing results showed that, before the DDOC and the DPOC, the dry-soot and smoke opacity efficiency decreases with the increase of substitution ratio of methanol at high engine load. There is a significant decrease of smoke opacity in DMDF mode after the DDOC, while the DPOC has a significant effect on the reduction in dry-soot emission. There is an average reduction in dry-soot by 25% in pure diesel fuel mode after the DDOC, while in DMDF mode, the average reduction is more than 60%, and the maximum reduction in dry-soot is up to 96%. There is a slightly reduction in PM emissions at low substitution ratio of methanol, while the high substitution ratio of methanol leads to more reduction in PM emissions. After the DDOC and the DPOC, particulate number and mass concentrations, especially nuclear particles, can be significantly reduced when the exhaust gas temperature is enough high.